2016
DOI: 10.1109/taslp.2016.2573591
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Likelihood PSD Estimation for Speech Enhancement in Reverberation and Noise

Abstract: In this contribution we focus on the problem of power spectral density (PSD) estimation from multiple microphone signals in reverberant and noisy environments. The PSD estimation method proposed in this paper is based on the maximum likelihood (ML) methodology. In particular, we derive a novel ML PSD estimation scheme that is suitable for sound scenes which besides speech and reverberation consist of an additional noise component whose second-order statistics are known. The proposed algorithm is shown to outpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 34 publications
0
88
0
Order By: Relevance
“…In the blocking-based method, the desired speech signal is first blocked using a blocking matrix (BM), and then the reverberation PSD is estimated. Estimators in this class are also based on the ML approach [1], [5], [7], [9] or the LS criteria [2], [4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the blocking-based method, the desired speech signal is first blocked using a blocking matrix (BM), and then the reverberation PSD is estimated. Estimators in this class are also based on the ML approach [1], [5], [7], [9] or the LS criteria [2], [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the noisy case, quality assessment was discussed in [9] and [14]. In [9], it was numerically demonstrated that an iterative blocking-based MLE yields lower MSE than the blocking-based LS estimator proposed in [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [20], we proposed a method to estimate the diffuse sound PSD using multiple reference signals, while we assumed at most one active source at a known position. In [21], a direct maximum likelihood estimate of the diffuse sound PSD given the observed signals was derived by assuming a noise-free signal model and using prior knowledge of the source position and the diffuse coherence. As the estimator presented in [21] considers only one sound source and no additive noise, we do not consider the estimator in the present work.…”
Section: Introductionmentioning
confidence: 99%